Investigating the relationship between Facebook addiction and cognitive emotion regulation strategies with the tendency to use drugs in middle school male students - Mitra Ebrahimi; Ahmed Kouhshekan; Ali Ebrahimi (University of Hormozgan, 2022)
The purpose of this article is to investigate the relationship between Facebook addiction and cognitive emotion regulation strategies with the tendency to use drugs in middle school male students of Lamard city (Iran). The method of study is correlation and statistical population includes all the male middle school students in Lamard in 2022. To estimate the sample size, we used the Krejcie-Morgan table and to select the sample, a multi-stage cluster sampling method was used, and at the end, 200 boys were selected as the sample. The research tool includes a questionnaire measuring the tendency to use drugs, which includes three subscales: readiness for addiction, recognition of addiction and alcoholism, which is extracted from the Minnesota Multifaceted Personality Inventory (MMPI-2), Cognitive Emotion Regulation (CERQ) and Bergen Facebook Addiction Scale (BFAS). Statistical data was analyzed through correlation coefficient by SPSS-18 software. Results indicated that students who use more negative strategies to reduce and cope with negative emotions tend to use temporary and ineffective alternatives such as the desire to consume drugs and alcohol. Also, excessive tendency towards Facebook can cause loneliness, anxiety and the desire to change one's identity in the virtual world.